(untitled) (New York, 1965)
This book provides extensive coverage of the basic structures and vocabulary of American English. The material consists of 80 units, each clearly laid out on a separate page. The Teacher's Book contains the complete Student Book interleaved with detailed teaching notes. These give step-by-step instructions for using the material, ideas for additional activities, and comprehensive suggestions on how to present each new topic
Keywords: English language,English language; United States